Assessment of patient satisfaction after facial aesthetic procedures with the combination of botulinum toxin a and hyaluronic acid fillers: a systematic review - Miranda, Idélcena Tatiane (2020)
Objective: A systematic review was performed to evaluate the satisfaction with the facial appearance of patients undergone facial aesthetic procedures with BTX-A and HA fillers. Material and Methods: This study was registered on International Prospective Register of Systematic Reviews (PROSPERO) database under the number (CRD42020184677) and follow the PRISMA recommendations. A comprehensive search was carried out in the MEDLINE via Pub-Med, Scopus, Web of Science, LILACS, BBO and Cochrane Library. In addition, the gray literature was also researched. The risk of bias tools from the Cochrane Collaboration and the Newcastle-Ottawa Quality Assessment Form for nonrandomized studies were used by two independent reviewers for quality assessment of the studies. Results: A total of 1187 studies were identified, 16 remained in qualitative study, 9 of these studies were considered at “unclear” risk of bias and 7 studies were “low” risk of bias. The studies compared the patient satisfaction about their facial appearance before and after treating full-facial or specific areas with BTX-A and HA using Face-Q, GAIS and other scales and the follow-up mean time was 6 months. Even with different scales, treated areas and follow-up time most of the subjects in the studies were satisfied or very satisfied with their facial appearance improvement after treatment. Conclusion: The results of the studies included in this systematic review suggested that the combination of BTX-A and HA procedures increase patient satisfaction with their facial appearance. However, more standardized studies are necessary to support these findings.